On Stories of Life, Death, and Resilience: Human-Animal Bonds for a Multispecies Becoming-With (KULT_online, 2020)
Susan McHugh’s Love in a Time of Slaughters: Human-Animal Stories against Genocide and Extinction (2019) maps out a radical path for future endeavors in literary animal studies. Inquiring into the affordances of narrative to engage in the preservation of cultural and biological diversity, McHugh unravels the entanglements between fictions featuring old or traditional ways of life and the modern-industrial world-views playing into their composition and reception. The analyzed films, novels, art installations, and truth commissions revisit genocide and extinction while focusing on their devastating impacts on human-animal bonds. Referring to these representations of interspecies affection, McHugh frames ‘love’ as a source of traditional knowledge on human-animal relationships and thus as a powerful force of resilience in an age when ‘slaughter’ constitutes a ubiquitous threat to peoples, species, and entire ecosystems. Her application of Indigenous metaphysics to her analyses paired with her consideration of socio-political dimensions transport Love in a Time of Slaughter right into the center of her discipline’s most cutting-edge scholarship.